HUBUNGAN DUKUNGAN SOSIAL DENGAN MOTIVASI BELAJAR SISWA DALAM MENGIKUTI PEMBELAJARAN ONLINE PADA MASA PANDEMI COVID-19 DI SMK YARSI MEDIKA TAHUN 2021 - Sundari, Uci; Sari, Cucuk Kunang; Sari, Rina Puspita (Nusantara Hasana Journal, 2022)
Learning motivation is a desire or desire that grows within the individual to obtain good results, especially in the learning process. In a pandemic situation like this, it has had such a big impact, especially in the education sector. The online learning policy has been implemented in Indonesia, with approximately 28.6 million students from elementary to high school/vocational school in various provinces. Realizing the importance of learning motivation, it is necessary to have social support from the closest people because the support provided can affect the increase in student learning motivation. The purpose of this study was to determine the relationship between social support and students' learning motivation in participating in online learning during the COVID-19 pandemic at Yarsi Medika Vocational School in 2021. The type of research used in this study was quantitative research with a descriptive correlation design and this study used a cross-sectional approach, the research sample is students of SMK Yarsi Medika class XI as many as 127 respondents and the sampling was done by "simple random sampling. The data analysis technique used is univariate and bivariate analysis. The results of the univariate test obtained social support in the low category as many as 70 people (55.1%), and learning motivation in the low category as many as 79 people (62.2%). The results of the Chi square test were obtained (P-value 0.000 â‰¤ 0.05), which means that there is a relationship between social support and students' learning motivation in participating in online learning during the COVID-19 pandemic at Yarsi Medika Vocational School. It is hoped that schools, especially teachers who teach, make more modifications in learning techniques so that students do not get bored quickly and students' motivation to learn remains good even though they are learning online.